A Study on the Quality Characteristics of Gongura Mutton Curry - An Ethnic Meat Product of Andhra Pradesh, India : 10.5958/2581-6616.2020.00004.3 - Indumathi, J.; Babu , A. Jagadeesh; Reddy, G. V. Bhaskar (Journal of Meat Science, 2021)
Mutton curry with gongura (Hibiscus sabdariffa L), a popular traditional Andhra Pradesh’s recipe, was prepared by using deboned mutton chunks and spices. Evaluated the effect of three different levels(20,40 & 60% ) of gongura incorporation on the quality of mutton curry at refrigeration temperature(4±1 0 C) for 20 days based on the proximate composition, pH, thiobarbituric acid reactive substances (TBARS), free fatty acid value (FFA), sensory attributes and microbiological assay. Results were revealed that,on increase in the addition gongura level in the product, the moisture, fibre and ash contents were (P<0.05) increased where as protein and fat contents were(P<0.05) decreased. Among the treatments, T3 (Mutton curry with 60% added gongura) scored significantly (P<0.05) lower overall mean pH, TBARS, FFA and microbiological values than control and other treatments during the entire storage period. However, T2 (Mutton curry with 40% added gongura) scored significantly (P<0.05) better scores for sensory evaluation than T3. Irrespective of the treatments the overall mean scores of appearance, flavour, mouth coating, sourness and overall acceptability were decreased significantly (P<0.05) on storage. It is concluded that mutton curry with gongura has better acceptable sensory quality characteristics up to 20 days of storage at refrigeration.